Does advanced maternal age explain the longer hospitalisation of mothers after childbirth? - Šťastná, Anna; Šídlo, Luděk; Kocourková, Jiřina; Fait, Tomáš (PloS one, 2023)
BACKGROUND: Fertility postponement, which has comprised the most significant reproductive trend in developed countries over the last few decades, involves a number of social, personal and health consequences. The length of stay (LOS) in hospital following childbirth varies considerably between countries. Czechia, where the fertility postponement process has been particularly dynamic, has one of the longest mean LOS of the OECD member countries. OBJECTIVE: We analyse the influence of the age of mothers on the LOS in hospital associated with childbirth. DATA AND METHODS: We employed anonymised individual data provided by the General Health Insurance Company of the Czech Republic on women who gave birth in 2014. Kaplan-Meier survival plots and binary logistic regression were employed to identify factors associated with long stays (> = 7 days for vaginal births, > = 9 days for CS births). RESULTS: The impact of the maternal age on the LOS is U-shaped. A higher risk of a longer hospitalisation period for young mothers was identified for both types of birth (OR = 1.58, 95% CI 1.33-1.87, p˂0.001 for age less than 20, OR = 1.31, 95% CI 1.20-1.44, p˂0.001 for age 20-24 compared to 30-34). The risk of a longer stay in hospital increases with the increasing age of the mother (OR = 1.23, 95% CI 1.13-1.35, p˂0.001 for age 35-39, OR = 2.05, 95% CI 1.73-2.44, p˂0.001 for age 40+ compared to 30-34), especially with concern to vaginal births. CONCLUSION: The probability of a long LOS increases significantly after the age of 35, especially in the case of vaginal births. Thus, the fertility postponement process with the significant change in the age structure of mothers contributes to the increase in health care costs associated with post-birth hospitalisation.
Keywords: Young Adult; Length of Stay; Maternal Age; mladý dospělý; Parturition; Pregnancy; těhotenství; vedení porodu; Mothers; Adult; dospělí; délka pobytu; lidé; ženské pohlaví; Humans; věk matky; Delivery, Obstetric; porod; Female; matky